Does stress shorten your life? Evidence from parental bereavement - Bernhard Schmidpeter (RWI - Leibniz-Institut für Wirtschaftsforschung, 2019)
This paper studies how stress affects the mortality risk. Using a flexible approach and allowing for timevarying treatment effects, I find no impact of stress on the short-run mortality risk but a substantially increase in the long-run. The effects are especially pronounced for men. I provide evidence that this is likely caused by changes towards adverse health behaviours as a reaction to stress. Investigating the possible protective effects of mental health support, I find that it can substantially lower the mortality risk for women. The results for men point towards lower effectiveness likely due to stigma effects associated with mental health care. Finally, I show that my results are robust to specific departure of my identifying assumptions. – – In diesem Papier analysiere ich den Einfluss von Stress auf das Mortalitätsrisiko. Ich verwende dazu einen flexiblen Ansatz, der es mir erlaubt, die Effekte von Stress über den Zeitverlauf zu messen. Meine Ergebnisse zeigen, dass sich Stress nicht auf das kurzfristige Mortalitätsrikisko auswirkt, aber zu einer deutlichen Erhöhung der langfristigen Mortalität führen kann. Diese Effekte sind für Männer besonders stark ausgeprägt. Ich zeige, dass gesundheitsschädliches Verhalten als Reaktion zu Stress ein wahrscheinlicher Grund hinter dieser Entwicklung ist. Psychologische Unterstützung in Verbindung mit Stress vermindert hingegen das Mortalitätsrisiko für Frauen. Ich finde eine geringere Wirksamkeit für Männer, wahrscheinlich aus Gründen von Stigmata, die mit psychologischer Unterstützung assoziiert sind. Die Ergebnisse sind robust zu spezifischen Abweichungen von meinen Identifikationsannahmen.
Keywords: I12; I11; C31; C41; 330; stress; mortality; mental health; bereavement; propensity score weighting; adjusted Kaplan-Meier Estimator; direct effects; indirect effects